Cooking Pots: Scales of Distribution and Modes of Production in the Roman East - Warner Slane, Kathleen (Rei Cretariae Romanae Fautorum Acta, 2015)
Cooking pots, because they are coarse in texture and often thick-walled, used to be dismissed as non-specialized, local products, manufactured where they were found. This is clearly a mistaken idea. Particular kinds of cooking pots were almost as widely distributed as fine wares in the Mediterranean, beginning in the later Republican period and continuing into Late Antiquity. Although the Republican “orlo bifido” pans and later Pompeiian-red ware pans are found so infrequently on some sites that they may have been distributed as one-offs or novelties, for motives of status or nostalgia rather than economics, their regular appearance at other sites shows that such widely distributed cooking vessels were a commodity in the eastern Mediterranean as well as the west. Recent investigations have also shown that particular mineral tempers have superior resistance to thermal shock, which suggests a reason for long-distance trade, although other factors related both to mechanical properties of the vessels and to social factors may also lie behind long-distance distribution. During the Roman imperial period long-distance trade in cooking pots is limited to a handful of cases in the East, however; most sites were supplied on a more local basis. This paper first describes the supply of cooking pots at Corinth from the Hellenistic through the middle Byzantine periods and suggests how production was organized in light of this evidence. Similar production patterns also exist elsewhere, and I will suggest that they are a Roman phenomenon, perhaps a symptom of how economies changed as a result of Roman interventions.